Hermeneutika Alquran: Model Interpretasi Nasr Hamid Abu Zayd - Lutfi, Muhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
This article discusses the methodology of reading the Qur’an initiated by Nasr Hamid Abu Zayd. As part of Islamic discourse, especially in the Qur’an, Nasr Hamid’s approach has sparked various productive discussions in the academic world. The approach of Nasr Hamid does not only contain its own characteristics, more than that, it is possible to produce an understanding, which at a certain point, has a power of social transformation. Two important issues as an example of the results of the approach are provided with some analyses on the matter of inheritance and slavery. It then must be understood in various aspects and contexts, and thus prompted to emerge an ideal egalitarian community. In this, Nas}r H{a>mid calls his hermeneutic approach as dialectics between ma‘na and maghza.